Universe, human immortality and future human evaluation - Bolonkin, Alexander (Elsevier insights., 2012)
This book debates the universe, the development of new technologies in the 21st century and the future of the human race. Dr Bolonkin shows that a human soul is only the information in a person's head. He offers a new unique method for re-writing the main brain information in chips without any damage to the human brain. This is the scientific prediction of the non-biological (electronic) civilization and immortality of the human being. Such a prognosis is predicated upon a new law, discovered by the author, for the development of complex systems. According to this law, every self-copying system tends to be more complex than the previous system, provided that all external conditions remain the same. The consequences are disastrous: humanity will be replaced by a new civilization created by intellectual robots (which Dr Bolonkin refers to as "E-humans" and "E-beings"). These creatures, whose intellectual and mechanical abilities will far exceed those of man, will require neither food nor oxygen to sustain their existence. They may have the emotion. Capable of developing science, technology and their own intellectual abilities thousands of times faster than humans can, they will, in essence, be eternal.